2007
DOI: 10.1007/s11258-007-9296-7
|View full text |Cite
|
Sign up to set email alerts
|

Effect of minor water depth treatments on competitive effect and response of eight wetland plants

Abstract: Two facets of plant competition, competitive effect (CE) and competitive response (CR), can be used to explain plant community composition but our understanding of abiotic factors that may differentially affect species’ competitive ability is incomplete. We tested whether water-depth affected CE (ability to suppress neighbour) and CR (avoid suppression from neighbour), and if so whether there was consistence in the rank order of both measures of competition under different water depth treatments. CE and CR we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
4
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 63 publications
1
22
4
1
Order By: Relevance
“…This is strong evidence that the relative competitive effect abilities among species do not vary strongly through plant development, and is consistent with studies showing that competitive effect ability is generally independent of both target plant identity and nutrient conditions (Fraser and Miletti 2008;Goldberg and Landa 1991;Wang et al 2010). Competitive effect ability is correlated with traits such as plant height and size, leaf shape, and relative growth rate (Goldberg 1996;Goldberg and Fleetwood 1987;Goldberg and Landa 1991;Keddy et al 2002).…”
Section: Competitive Effect and Response And Plant Agesupporting
confidence: 84%
See 2 more Smart Citations
“…This is strong evidence that the relative competitive effect abilities among species do not vary strongly through plant development, and is consistent with studies showing that competitive effect ability is generally independent of both target plant identity and nutrient conditions (Fraser and Miletti 2008;Goldberg and Landa 1991;Wang et al 2010). Competitive effect ability is correlated with traits such as plant height and size, leaf shape, and relative growth rate (Goldberg 1996;Goldberg and Fleetwood 1987;Goldberg and Landa 1991;Keddy et al 2002).…”
Section: Competitive Effect and Response And Plant Agesupporting
confidence: 84%
“…Importantly, other studies have shown a lack of correlation between competitive effect and response abilities (Fraser and Miletti 2008;Goldberg and Landa 1991;Keddy et al 1994). We suggest that the form of competition occurring is important in determining whether there is a positive relationship between competitive effect and response.…”
Section: Competitive Effect and Response And Plant Agementioning
confidence: 53%
See 1 more Smart Citation
“…Relative competitive index (RCI), relative neighbour effect Brooker et al (2005), Grace (1995), Turkington et al (1993), Campbell & Grime (1992), Wilson & Tilman (1995), Fraser & Miletti (2008), Markham & Chanway (1996) …”
Section: Competitive Intensitymentioning
confidence: 99%
“…We expected Typha treatments to lower light penetration and temperature at the soil surface (Angeloni et al 2006;Hager 2004) and to decrease native plant Herman et al (2001) and P values calculated using two-tailed t tests species' abundances (Frieswyk et al 2007;Tuchman et al 2009;Zedler and Kercher 2004). We anticipated negative, intraspecific effects of Typha density and Typha litter on the biomass of individual Typha plants and overall Typha biomass (Gurevitch et al 1992;Holly and Ervin 2006) and hypothesized that waterlevel treatments would have species-specific effects on native plant biomass (Fraser and Miletti 2008;Weiher and Keddy 1995).…”
Section: Introductionmentioning
confidence: 97%